1994
DOI: 10.1017/s0021859600067800
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen mineralization, nitrate leaching and crop growth after ploughing-in leguminous and non-leguminous grain crop residues

Abstract: A field experiment was conducted in Canterbury, New Zealand to investigate the effect of six leguminous and non-leguminous grain crops on soil N fertility over a 12 month period (March 1989 to March 1990. All crops had an overall negative N balance during their growing season. A greater amount of soil N was removed by barley, rape and lupins (104-119 kg N/ha) than by field beans, field peas or lentils (50-74 kg N/ha).Net N mineralization was measured in all treatments between residue incorporation and the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 13 publications
2
16
1
Order By: Relevance
“…Soil conditions suitable for N mineralization after late autumn incorporation was concluded to last generally too short time under Finnish conditions to result in substantial net N mineralization before spring. Thus the release of N from incorporated plant biomass during the following summer can be essential for the yield of the following crop, accordingly to Francis et al (1994), who found that grain yield of spring wheat correlated positively with net N mineralization during the growing season after crops with a different N content. Francis et al (1994) also found that grain yield of spring wheat correlated positively with soil mineral N content before the growing season.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Soil conditions suitable for N mineralization after late autumn incorporation was concluded to last generally too short time under Finnish conditions to result in substantial net N mineralization before spring. Thus the release of N from incorporated plant biomass during the following summer can be essential for the yield of the following crop, accordingly to Francis et al (1994), who found that grain yield of spring wheat correlated positively with net N mineralization during the growing season after crops with a different N content. Francis et al (1994) also found that grain yield of spring wheat correlated positively with soil mineral N content before the growing season.…”
Section: Discussionmentioning
confidence: 91%
“…Thus the release of N from incorporated plant biomass during the following summer can be essential for the yield of the following crop, accordingly to Francis et al (1994), who found that grain yield of spring wheat correlated positively with net N mineralization during the growing season after crops with a different N content. Francis et al (1994) also found that grain yield of spring wheat correlated positively with soil mineral N content before the growing season. In the present study however, the yield could not be deduced from the soil N contents, as in general spring barley yields were similar after early and late autumn ploughing.…”
Section: Discussionmentioning
confidence: 91%
“…The type of the preceding crop affects the amount of residual N during autumn available for leaching. Francis et al (1994) reported from an experiment using rotations with legume and non-legume crops and spring crops that the amount of mineral N remaining in the soil profile in the autumn after harvest of barley and rapeseed crops was about 52 kg N ha −1 . However, after leguminous crops, the residual N was generally larger (mean of 80 kg N ha −1 ).…”
Section: Management Effectsmentioning
confidence: 99%
“…Generally, plant residues with an N content of less than 1.2-1.3% (C:N ratio of about 30) will immobilize soil N (and fertilizer N, if present); however, if the percent N is more than 1.8-2.0 (C:N ratio of about 20), considerable mineralization usually occurs (Jenkinson 1981;Janzen and Kucey 1988). Indirect calculations of net N mineralization (wheat total N yield minus preseeding soil nitrate-N levels), suggested greater mineralization after a legume than non-legume crop (Francis et al 1994). In a laboratory study, Jensen (1996) found greater mineralization of N in soils collected from field pea than barley (Hordeum vulgare L.) stubble.…”
Section: Mots Clésmentioning
confidence: 99%